Super Ultrawideband Planar Inverted F Antenna on Paper based Substrate with Low SAR - Kumari, Sakshi; Gupta, Vibha Rani (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2019)
In this paper, a super ultrawide band planar inverted F antenna (PIFA) has been proposed for wearable applications on a low cost, ecofriendly paper-based substrate. This work is a first and important step towards the progression of conformal flexible antennas for a body area network. The proposed antenna has measured impedance bandwidth of 10.6 GHz, which covers almost all the bands of a wireless body area network i.e. GSM (880-960 MHz), GPS (1565-1585 MHz), DCS (1710-1880 MHz), PCS (1850-1990 MHz), UMTS (1920-2170 MHz), ISM (2.4-2.4835 GHz), WiMAX (3.3-3.8 GHz), HIPERLAN (5.15-5.35 GHz), WLAN (5.725-5.850 GHz) and UWB (3.1-10.6 GHz). Initially, the electrical characteristics of paper are extracted using Cavity Resonator and Transmission line method and then used for the design and fabrication of the proposed antenna. The measured results are in good agreement with the simulated results. This paper also focuses on analysis of the effect of electromagnetic absorption in terms of specific absorption rate for a human arm with frequency exposure at 0.9 GHz, 1.5 GHz, 1.8 GHz, 3.5 GHz, 2.45 GHz, 5.2 GHz and 5.8 GHz and is found to be within the recommended limit by FCC.